Atomically Dispersed Transition Metals on Carbon Nanotubes with Ultrahigh Loading for Selective Electrochemical Carbon Dioxide Reduction. Issue 13 (9th February 2018) - Cheng, Yi; Zhao, Shiyong; Johannessen, Bernt; Veder, Jean‐Pierre; Saunders, Martin; Rowles, Matthew R.; Cheng, Min; Liu, Chang; Chisholm, Matthew F.; De Marco, Roland; Cheng, Hui‐Ming; Yang, Shi‐Ze; et al.
Abstract: Single‐atom catalysts (SACs) are the smallest entities for catalytic reactions with projected high atomic efficiency, superior activity, and selectivity; however, practical applications of SACs suffer from a very low metal loading of 1–2 wt%. Here, a class of SACs based on atomically dispersed transition metals on nitrogen‐doped carbon nanotubes (MSA‐N‐CNTs, where M = Ni, Co, NiCo, CoFe, and NiPt) is synthesized with an extraordinarily high metal loading, e.g., 20 wt% in the case of NiSA‐N‐CNTs, using a new multistep pyrolysis process. Among these materials, NiSA‐N‐CNTs show an excellent selectivity and activity for the electrochemical reduction of CO2 to CO, achieving a turnover frequency (TOF) of 11.7 s −1 at −0.55 V (vs reversible hydrogen electrode (RHE)), two orders of magnitude higher than Ni nanoparticles supported on CNTs. Abstract : A novel atomically dispersed transition‐metal single‐atom catalyst supported on carbon nanotubes is synthesized with atomic loading as high as 20 wt%, excellent selectivity, and activity for the electrochemical reduction of carbon dioxide.